Dampak Kenaikan Angka Inflasi dan Faktor Produk Domestik Regional Bruto (PDRB) Terhadap Masalah Pengangguran di Sumatera Utara dalam Jangka Waktu 2010-2020 - SINAGA, HARI JAYA (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study aims to determine the level and size of unemployment in North Sumatra, which is affected by inflation and GRDP (Gross Regional Domestic Product) simultaneously and partially during 2010-2020.In quantitative research methods, 330 observations are used to measure multiple linear regression, and the results for the regression equation: Y = 5.81 + 0.10 X1 - 0.08 X2. In the t-test, the result of t-Count > t-Table (8.670182 > 1.649949) shows that inflation has a positive and significant effect and significance on the unemployment rate, and the result of -t Count < -t Table (-4.233704 < -1.649949) shows that GRDP has a negative value and significant effect on the unemployment rate. It also shows that inflation and GERD can influence the occurrence of inflation. The R2 quadratic test result of 0.454794 shows that inflation and GRDP contribute 45.47% to the unemployment rate. In contrast, the remaining 54.53% are brought about by additional variables that are not part of this research model